2017
DOI: 10.1186/s13071-017-2367-2
|View full text |Cite
|
Sign up to set email alerts
|

Microarchitecture of the tsetse fly proboscis

Abstract: BackgroundTsetse flies (genus Glossina) are large blood-sucking dipteran flies that are important as vectors of human and animal trypanosomiasis in sub-Saharan Africa. Tsetse anatomy has been well described, including detailed accounts of the functional anatomy of the proboscis for piercing host skin and sucking up blood. The proboscis also serves as the developmental site for the infective metacyclic stages of several species of pathogenic livestock trypanosomes that are inoculated into the host with fly sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Haarløv () concluded that L. cervi is a pool feeder and not a capillary feeder like some mosquitoes because it needs to injure the skin of the host in order to suck blood from a haemorrhage made by its teeth. Lipoptena fortisetosa shows mouthpart structures that are the same as those in L. cervi and both are very similar to the feeding apparatus of the Glossinidae (Snodgrass, ; Haarløv, ; Krenn & Aspöck, ; Gibson et al ., ). The mouthparts of tsetse flies include a proboscis that is equipped with arrays of teeth and rasps.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Haarløv () concluded that L. cervi is a pool feeder and not a capillary feeder like some mosquitoes because it needs to injure the skin of the host in order to suck blood from a haemorrhage made by its teeth. Lipoptena fortisetosa shows mouthpart structures that are the same as those in L. cervi and both are very similar to the feeding apparatus of the Glossinidae (Snodgrass, ; Haarløv, ; Krenn & Aspöck, ; Gibson et al ., ). The mouthparts of tsetse flies include a proboscis that is equipped with arrays of teeth and rasps.…”
Section: Discussionmentioning
confidence: 97%
“…The mouthparts of tsetse flies include a proboscis that is equipped with arrays of teeth and rasps. The proboscis is formed by labella at the top of the organ and is divided lengthwise into a labrum and a labium that includes the hypopharynx (Gibson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Naturally, from a human and economic point of view, it is the mammalian infection stage that has attracted most attention in the past. It is only more recently that the parasite-vector interaction and biology has received more detailed attention and that also non- T. brucei infections have been studied in tsetse ( 73 , 74 ). These reports show that in fact both T. congolense and T. vivax are much more effective in establishing tsetse infections than T. brucei .…”
Section: General Life Cycle Of Salivarian Trypanosomes and Interactiomentioning
confidence: 99%
“…Compared to the available knowledge of the T. brucei life cycle, the cycle of other salivarian trypanosomes is less well documented [30][31][32]. Interestingly T. congolense is Figure 1.…”
Section: Figurementioning
confidence: 99%